2015
DOI: 10.3111/13696998.2015.1061534
|View full text |Cite
|
Sign up to set email alerts
|

Health resource use and costs of vilazodone and other selective serotonin re-uptake inhibitors in treating major depressive disorder

Abstract: MDD treatment with vilazodone was associated with significantly lower rates of inpatient and emergency services, and with significantly lower all-cause medical service costs and numerically (non-significantly) lower total costs to payers than with the other SSRIs included in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…A study conducted among individuals with depression in the United States showed similar results. The researchers reported that a higher proportion of females were using antidepressants, specifically selective serotonin reuptake inhibitors [ 13 ]. However, other studies have shown different results.…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted among individuals with depression in the United States showed similar results. The researchers reported that a higher proportion of females were using antidepressants, specifically selective serotonin reuptake inhibitors [ 13 ]. However, other studies have shown different results.…”
Section: Discussionmentioning
confidence: 99%